1995
DOI: 10.1210/en.136.12.5385
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the thyroid hormone transport system and the Na(+)- H+ exchanger in cultured rat brain astrocytes

Abstract: The entry of T3 and T4 into rat cultured astrocytes is mediated by a sterospecific saturable transport system. This study examines the effect of inhibiting the Na(+)-H+ exchanger and intracellular acidification on the initial velocity of [125I]T3 and [125I]T4 uptake. The resting intracellular pH (pHi) was approximately 7.15 in astrocytes exposed to CO2/HCO3(-)-free medium buffered with HEPES at pH 7.40 at 22 C. Isoosmotic replacement of extracellular sodium by mannitol or choline decreased the pHi by 0.15 pH u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Similar to hepatocytes, apparent Km values for the high-affinity uptake of T 3 in other cell types are mostly in the nanomolar range. Some authors(22,73),…”
mentioning
confidence: 99%
“…Similar to hepatocytes, apparent Km values for the high-affinity uptake of T 3 in other cell types are mostly in the nanomolar range. Some authors(22,73),…”
mentioning
confidence: 99%
“…Moreover, in hepatic cells, uptake of TH has been induced by the Na + /TA transporting polypeptide (NTCP) and OATP1 (Friesema et al, 1999 ), which are both found to be expressed at low levels in the rat CP (Choudhuri et al, 2003 ). Furthermore, the sodium-dependent mechanism of TH has been demonstrated in rat skeletal muscle (Centanni and Robbins, 1987 ), human glioma cells (Goncalves et al, 1990 ), rat glial cells (Francon et al, 1989 ), astrocytes (Beslin et al, 1995 ), and cerebrocortical neurons (Chantoux et al, 1995 ). Finally, as a consequence of low sodium effect in this study and results of another study (Kassem et al, 2006 ), the abundant presence of 125 I-T 4 in CSF suggests a partial rapid diffusion of 125 I-T 4 into tissue that is driven by a bulk flow of CSF and receptor-mediated endocytosis (Kassem et al, 2006 ).…”
Section: Discussionmentioning
confidence: 99%